Inter-annual and intra-annual tree-ring oxygen isotope signals in response to monsoon rainfall in northwestern Thailand - Preechamart S. (2023)
We present a new teak (Tectona grandis L.f.) tree-ring stable oxygen isotope (δ18OTR) chronology from Mae Tuen (MT) site, Tak province, northwestern Thailand at inter-annual (167-year, A.D.1850–2016) and intra-annual (A.D.2006–2016) timescales. The inter-annual δ18OTR chronology showed a significant negative correlation (r = −0.678, p < 0.01) with the May–October amount of regional rainfall obtained from CRU TS4.03. We established a linear regression model that explained 46.0% of the actual rainfall variance and reconstructed monsoon season rainfall back to A.D.1850. The seasonal variations in moisture conditions were reflected in inter-annual δ18OTR variability. The rainfall amount and δ18O in precipitation (δ18Op) mainly controlled intra-annual variations in teak δ18OTR. These results show that the variation in Thai teak δ18OTR is dominated by rainfall, highlighting the strength of δ18OTR as a monsoon rainfall proxy.